Mengenal Tudung Lingkup Kebudayaan dari Jambi Kota Seberang - Nurlaila, Putri; Destrinelli, Destrinelli (Lembaga Yasin AlSys, 2023)
This article discusses the cultural scope of hoods originating from Jambi, especially from the city of Seberang. The scope cover is a type of head covering used by women in Jambi culture. This article describes the origins, functions, and variations of the hood as well as its importance in strengthening the cultural identity of the people of Jambi. Through studies of Jambi culture, the author identifies the hood as a symbol of elegance, modesty, and the majesty of Jambi women. This head covering has a unique shape, usually made of Jambi silk or cloth which is decorated with intricate and beautiful traditional motifs. This article also discusses the role of the scope veil in Jambi society, including in traditional ceremonies, weddings and other cultural events. The author highlights the importance of preserving the tradition of using the hood as part of Jambi's cultural identity, as well as maintaining the sustainability of the valuable cultural heritage. In addition, this article highlights variations of the hood from the city of Seberang Jambi. Although the basic form is similar, there are variations in design, color, and decoration that distinguish Jambi hoods from other regions in Indonesia. This shows the cultural richness and uniqueness of the city of Seberang Jambi. In order to promote and preserve this cultural heritage, this article also invites the public to appreciate and learn more about hoods from Jambi, especially from the city of Seberang. It is hoped that through knowledge and appreciation of this culture, wider awareness can be created to maintain the continuity of Jambi's traditions and cultural wealth.